Improving the Creative Process Strategy of the Specialty Coffee in Eastern Province Saudi Arabia in Strengthening Sustainability in the Coffee Value Chain - Kurniawan Arif Maspul (CV. Ulil Albab Corp, 2022)
The progress of the coffee trend globally is one of the options for developing SMEs in Eastern Province, Saudi Arabia. The third-wave generation of specialty coffee is growing with a large selection of artisanal coffee drinks, empowering the latest generation to follow the coffee industry's value chain through coffee skills and sustainability. Sustainability in the coffee value chain will be connected to the three-bottom legs that make it sustainable in the social economy and environment. Eastern Province has the potential to become a coffee hub in tackling challenges in the coffee value chain. Still, stakeholder empowerment is needed for coffeeprenuers in Eastern Province to make coffee value chains resilient collaboratively. Creative process strategies are required to investigate the advancement in ideas and innovations. This qualitative descriptive study will help the catch in opening the eyes of the global coffee community and especially in Saudi Arabia, in seeing the opportunity for the coffee value chain in the region.